2019
DOI: 10.15171/ijhpm.2019.54
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Enrolment of Households in Nepal’s National Health Insurance Program

Abstract: Background: Nepal has made remarkable efforts towards social health protection over the past several years. In 2016, the Government of Nepal introduced a National Health Insurance Program (NHIP) with an aim to ensure equitable and universal access to healthcare by all Nepalese citizens. Following the first year of operation, the scheme has covered 5 percent of its target population. There are wider concerns regarding the capacity of NHIP to achieve adequate population coverage and remain viable. In this contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 33 publications
9
35
3
Order By: Relevance
“…Other reasons might be elderly population wants future health security in their life and Government of Nepal is also protecting elder population by subsidizing the premium of geriatric population aged above 70 years. Existing literatures of Nepal and Ghana are similar with the present study (Adhikari et al, 2019;Badu et al, 2018;Jehu-Appiah et al, 2011) however another literature of the Nepal showed the contradictory result (Ghimire et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Other reasons might be elderly population wants future health security in their life and Government of Nepal is also protecting elder population by subsidizing the premium of geriatric population aged above 70 years. Existing literatures of Nepal and Ghana are similar with the present study (Adhikari et al, 2019;Badu et al, 2018;Jehu-Appiah et al, 2011) however another literature of the Nepal showed the contradictory result (Ghimire et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Facts from various studies have shown the positive association between socio-economic status and non-enrollment (Ghimire et al, 2019;Jehu-Appiah et al, 2011;Mirach et al, 2019;Paudel, 2019). The present study also showed that non-enrollment increases with the decreasing socio-economic status in the society.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In Nepal, the concept of health insurance is at a preliminary stage and in the year 2016, the government introduced a national health insurance program which covered just 5% of the population 22 and hence consumers pay out-of-pocket to purchase medicines. Being a country with poor socioeconomic status any wastage of medicines can negatively impact healthcare affordability.…”
Section: Discussionmentioning
confidence: 99%
“…On demand side, socio demographic factors like education, economic status, access to health care facilities etc. are seen responsible for health care utilization in health insurance, but these studies are in small scale [28][29][30][31]. A study conducted by Nepal Health Research Council (NHRC) suggests that insured > 90% want to renew the health insurance scheme if it increases the coverage of the service package.…”
Section: Theoretical Groundingsmentioning
confidence: 99%